Evaluation of distinct soft-sediment deformation triggers in mixed carbonate-siliciclastic systems: Lessons from the Brazilian Pre-Salt analogue Crato Formation (Araripe Basin, NE Brazil) - Varejão, F. G.; Warren, L. V. [UNESP]; Simões, M. G. [UNESP]; Cerri, R. I. [UNESP]; Alessandretti, L.; Santos, M. G.M.; Assine, M. L. [UNESP] (Elsevier, 2022)
Soft-sediment deformation structures (SSDSs) are ubiquitous in several depositional sedimentary environments and can be triggered by autogenic- and allogenic-related mechanisms. SSDSs identification in the geological record is more frequent in siliciclastic deposits, from which the most accepted models were developed. Given the fact that carbonate rocks have rapid diagenesis, which results in changes in the rheological behavior of deformational processes in short time, these are excellent facies for exploring past deformational mechanisms in a given sedimentary basin. Here, we describe distinct SSDSs developed in mixed carbonate-siliciclastic successions deposited in an Early Cretaceous lacustrine depositional system (carbonate-dominated) subjected to recurrent epicontinental marine ingressions (siliciclastic-dominated). Deformation occur in some siliciclastic intervals but it is more common in carbonate beds. Facies associations analysis combined with detailed outcrop description of the SSDSs allowed the recognition of seismic- and non-seismic-generated structures. Two km-scale, laterally continuous carbonate beds, characterized by deformation-bearing horizons, are interpreted to be the result of seismic shocks. Conversely, most of the recognized SSDSs cannot be confidentially interpreted as seismites. Autogenic triggers and criteria for accessing the origin of deformation mechanisms in both carbonate- and siliciclastic-dominated settings are alternatively proposed. Assessing such criteria is fundamental for differentiatte the timing and range of deformation and are here discussed in the context of the offshore petroleum reservoirs in the Brazilian Pre-Salt successions, where lacustrine carbonates were probably subjected to a similiar superposition of syn-sedimentary seismicity and later events of salt-tectonics and hydrotermalism.
Keywords: Autogenic trigger; Crato formation; Lacustrine carbonate; Pre-salt analogue; Seismicity; Soft-sediment deformation